2015
DOI: 10.1039/c4ob02329c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective carbolithiation of S-alkenyl-N-aryl thiocarbamates: kinetic and thermodynamic control

Abstract: The addition of n-butyllithium to alkenylthiocarbamates in the presence of (-)-sparteine or the (+)-sparteine surrogate leads to asymmetric carbolithiation, and returns enantiomerically enriched thiocarbamate derivatives of secondary thiols. In THF, with the (+)-sparteine surrogate, in situ aryl migration leads to an enantiomerically enriched tertiary thiol derivative. Remarkably, the two pseudoenantiomeric chiral ligands do not always give enantiomeric products, probably as a result of a complex interplay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…To probe this, as ample of 1 was metalated at À67 8Ci n[ D 8 ]THF and the reactionf ollowed by 1 HNMR spectroscopy( Figure 3). [23] Before addition of base, the heterobenzylic protons of 1 appear at dH2 .79 ppm. After addition of LDA, two signals are clearly visible at dH2 .79 and dH 2.75 ppm, corresponding to residual 1 and the alkenyl proton of azaenolate taut-24.W hile this may at first glance appear unusually upfield for an sp 2 centre proton, this does correspond to the spectrum for the analogous enolate of dimethylacetamide 25 as reportedb yR athke (dH3 .16 and 2.93 ppm; Figure 4) and enolate 26 reported by Still (dH3 .50 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…To probe this, as ample of 1 was metalated at À67 8Ci n[ D 8 ]THF and the reactionf ollowed by 1 HNMR spectroscopy( Figure 3). [23] Before addition of base, the heterobenzylic protons of 1 appear at dH2 .79 ppm. After addition of LDA, two signals are clearly visible at dH2 .79 and dH 2.75 ppm, corresponding to residual 1 and the alkenyl proton of azaenolate taut-24.W hile this may at first glance appear unusually upfield for an sp 2 centre proton, this does correspond to the spectrum for the analogous enolate of dimethylacetamide 25 as reportedb yR athke (dH3 .16 and 2.93 ppm; Figure 4) and enolate 26 reported by Still (dH3 .50 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of DMPU to these lithiated intermediates caused nitrogen‐to‐carbon aryl migration to afford enantioenriched benzylic tertiary amine derivatives, which could be hydrolyzed to the chiral tertiary alkyl amines. The reaction was successfully extended to carbamates and thiocarbamates, although enantioselective rearrangement was more challenging for these substrates …”
Section: Two‐electron Smiles Rearrangementmentioning
confidence: 99%
“…The reactionw as successfully extended to carbamates and thiocarbamates,a lthough enantioselectiver earrangement was more challenging for these substrates. [66][67][68] Scheme39. Chiral auxiliary direct preparation of enantioenriched hydantoins.…”
Section: Scheme34 Lithiation/aryl Migration Of Ureas and (Thio)carbamentioning
confidence: 99%
“…[4][5][6] While stereospecific alkylation of chiral organolithiums is routine, [1] stereospecific arylation or alkenylation to form more functionalized products requires specialised approaches. [7][8][9][10][11] Building on our discovery that metallated N-benzyl-N'-aryl ureas, [12][13][14][15][16][17][18][19] carbamates, [20][21][22][23] and thiocarbamates [24][25][26] undergo stereospecific aryl migration to the carbanionic centre, we previously reported that the stereospecific N to C vinyl migration of a variety of lithiated benzylic ureas 3, carbamates 4 and thiocarbamates 5 may be used to generate -vinyl tertiary amines, alcohols and thiols from their parent compounds 1 after deprotection of the products 6-8 (Scheme 1a). [27] The N-vinyl substituted starting materials [14,17,[27][28][29][30] for this reported vinylation had been synthesized by a two-step procedure that employed vinyl isocyanate 2 to introduce the N-alkenyl substituent.…”
Section: Introductionmentioning
confidence: 99%